Ageing and the balance of care: an investigation into the relationship between and determinants of acute hospital bed and long -term care utilisation - Wren, Maev-Ann (Trinity College (Dublin, Ireland). Department of Economics, 2011)
The central theme of this thesis is the effect of ageing on the balance between acute and long-term care (LTC). The thesis comprises two separate but related enquiries. The first enquiry is an econometric analysis of the drivers of acute bed and long-term care utilisation across member countries of the Organisation for Economic Co-operation and Development (OECD). The second enquiry is an examination of long-term care supply and demand in Ireland which includes: analysis of the first comprehensive, longitudinal Irish data on disability prevalence; and the development of a statistical model predicting demand for residential long-term care, based on projected demographic change, trends in disability rates in older age and a policy of reconfiguring care from the acute to the community and long-term care sectors.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin